Cyber Security in Energy Distribution System: Exploring Challenges and Valuation of Real-Time Data Communication in Cyber Security for Energy Distribution Systems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Current era is of technology convergence, which is also redefining energy distribution system in the power sector. A telecommunication playing an important role in energy distribution, where it constitute of many electronic systems widely interconnected via a wired as well as wireless network.In this paper we cover majorly three aspects which include 1.To study challenges of Energy Distribution System2.To study role valuation of Real Time Data communication in melioration of operational financial efficiency for Energy Distribution Systems3.To study Cyber Security in Energy Sector